Long‐Term Medical and Psychosocial Outcomes in Living Liver Donors. Issue 4 (22nd December 2016) - Dew, M. A.; Butt, Z.; Humar, A.; DiMartini, A. F.
Abstract : Due to the enduring organ shortage, living donor liver transplantation has been a valuable treatment strategy for advanced liver disease patients for over 20 years. A variety of reviews have summarized the extensive data now available on medical and psychosocial risks to living donors in the aftermath of donation. However, evidence on donor medical and psychosocial outcomes beyond the first year postdonation has not been synthesized in any previous review. The evidence base on such "long‐term" outcomes has been growing in recent years. A review of this evidence would therefore be timely and could serve as an important resource to assist transplant centers in their efforts to fully educate prospective donors and gain informed consent, as well as develop appropriate postdonation clinical care and surveillance plans. We reviewed recent literature on long‐term donor outcomes, considering (a) medical outcomes, including mortality risk, rates of complications, abnormalities detected in laboratory testing, and the progress of liver regeneration; and (b) donor‐reported psychosocial outcomes reflecting physical, emotional, and interpersonal/socioeconomic well‐being, as well as overall health‐related quality of life. We summarize limitations and gaps in available evidence, and we provide recommendations for future research and clinical care activities focused on long‐term outcomes in liver donors. Abstract : The authors review and comment on the small but growing evidence base for long‐term outcomes in living liver donors, including key medical outcomes and donor‐reported psychosocial outcomes.